Coastal Themes (Terra Australis 24) An Archaeology of the Southern Curtis Coast, Queensland - Ulm, Sean (Terra Australis, 2006)
Coastal archaeology in Australia differs in many respects from that of other areas, with the potential to examine relatively fine-scale variation. Nevertheless, there has been a general tendency in Australian archaeology to play down the variability and to subsume the evidence into broader homogenising models of Aboriginal cultural change. This case study clearly and self-consciously addresses the need to focus on local and regional patterns before moving on to more general levels of explanation. Coastal Themes builds a detailed chronology of Aboriginal occupation for the southern Curtis Coast in Queensland. Innovative analyses refine radiocarbon dates and explore discard behaviours and post-depositional processes affecting the integrity of coastal archaeological sites. The resulting insights highlight major changes in Aboriginal use of this region over the last 5,000 years and disjunctions between the course of occupation in this and adjacent regions.